Trustee, State and Stakeholder: Hindu Temple Management in Contemporary India, 1957–2012. (January 2020) - Tanaka, Tetsuya
The literature on temple management in colonial and post-colonial India focusses on the dominant role of the trustees and the impact of state intervention. However, this article tries to grasp significance of the role of the stakeholders in the temple management as a bridge between the trustees and the state by analyzing the management history of the Rani Sati temple from 1957 to 2012. It will first explain the historical background of this temple and its managers, the Marwaris. The second section analyzes the form of the temple management from the 1950s to 1970s, and the judicial case against the traditional temple stakeholders, then chief priest and his family members. Because of the national controversy over sati in the late 1980s, public interest groups emerged as the new stakeholders of the temple. Third, this article clarifies the state's intervention in the temple's management according to the influence of new the stakeholders. By focussing on the role of the stakeholders, this article discloses how a state intervention can be initiated by the stakeholders and the possibility of transformation of the temple management. JEL: M14, K41, Z12